Global Analysis of Transcriptome and Translatome Revealed That Coordinated WNT and FGF Regulate the Carapacial Ridge Development of Chinese Soft-Shell Turtle - Jun Zhang (MDPI AG, 2021)
The turtle carapace is composed of severely deformed fused dorsal vertebrae, ribs, and bone plates. In particular, the lateral growth in the superficial layer of turtle ribs in the dorsal trunk causes an encapsulation of the scapula and pelvis. The recent study suggested that the carapacial ridge (CR) is a new model of epithelial–mesenchymal transition which is essential for the arrangement of the ribs. Therefore, it is necessary to explore the regulatory mechanism of carapacial ridge development to analyze the formation of the turtle shell. However, the current understanding of the regulatory network underlying turtle carapacial ridge development is poor due to the lack of both systematic gene screening at different carapacial ridge development stages and gene function verification studies. In this study, we obtained genome-wide gene transcription and gene translation profiles using RNA sequencing and ribosome nascent-chain complex mRNA sequencing from carapacial ridge tissues of Chinese soft-shell turtle at different development stages. A correlation analysis of the transcriptome and translatome revealed that there were 129, 670, and 135 codifferentially expressed genes, including homodirection and opposite-direction differentially expressed genes, among three comparison groups, respectively. The pathway enrichment analysis of codifferentially expressed genes from the Kyoto Encyclopedia of Genes and Genomes showed dynamic changes in signaling pathways involved in carapacial ridge development. Especially, the results revealed that the Wnt signaling pathway and MAPK signaling pathway may play important roles in turtle carapacial ridge development. In addition, Wnt and Fgf were expressed during the carapacial ridge development. Furthermore, we discovered that Wnt5a regulated carapacial ridge development through the Wnt5a/JNK pathway. Therefore, our studies uncover that the morphogenesis of the turtle carapace might function through the co-operation between conserved WNT and FGF signaling pathways. Consequently, our findings revealed the dynamic signaling pathways acting on the carapacial ridge development of Chinese soft-shell turtle and provided new insights into uncover the molecular mechanism underlying turtle shell morphogenesis.